An immunoassay cassette with a handheld reader for HIV urine testing in point-of-care diagnostics - Yang, Wenbo; Yang, Dianlong; Gong, Shisong; Dong, Xiaobing; Liu, Luyao; Yu, Shengda; Zhang, Xiaolei; Ge, Shengxiang; Wang, Dong; Xia, Ningshao; Yu, Duli; Qiu, Xianbo (Biomedical microdevices, 2020)
Currently, most HIV tests are performed with blood samples, or alternatively saliva samples are used for HIV testing. Simple HIV tests need to be performed in hospitals or other medical agencies instead of more invasive HIV blood tests. To enable point-of-care (POC) HIV diagnostics, based on a recently developed lateral flow strip for HIV urine testing, a microfluidic immunoassay cassette with a handheld optical reader is developed. Based on lateral flow strip with gold colloid reporter, the integrated immunoassay cassette can perform sample introduction, metering, discharging, applying and detection which simplifies HIV testing. An indicator is incorporated into the cassette to guide sample introduction based on color change, and further, the excess test sample is stored inside the sealed cassette to avoid any contamination. The low-cost handheld optical reader can provide a test result within a few seconds, which is useful for simple, sensitive and affordable HIV onsite detection. Instead of using normal white LEDs, a customized back light module embedded with green LEDs is adopted to illuminate the lateral flow strip with an appropriate working current to achieve optimal performance. Compared to the standard lateral flow strips using a benchtop reader, with the disposable immunoassay cassette assisted by the handheld optical reader, more convenient, easier-to-operate, and more affordable HIV urine testing can be achieved in POC diagnostics.